On Distributions of Order Statistics of Random Vectors - Gungor, M.; Turan, A. (Eudoxus Press, Llc, 2010)
In this study, the probability density and distribution functions of order statistics of the innid random vectors expressed as the probability density and distribution functions of order statistics of the iid random vectors using permanents. Moreover, we collect sonic results concerning the probability density and distribution functions of order statistics for the specialized cases.
Keywords: Order statistics; permanent; joint probability density function; joint distribution function; iid random variables; innid random variables; recurrence relations